EVALUASI ANGGARAN BIAYA PROYEK PEMASANGAN JARINGAN DISTRIBUSI PADA CV. EKATAMA PALEMBANG - Salmah, Ninin Non Ayu (Jurnal Media Wahana Ekonomika, 2012)
ABSTRAKThis research discusses about the evaluation of budget from the network distribution installation project in CV. Ekatama Palembang. The aim of this research is to recognise whether the realisation of the budget has been aproppriate with the budget determined previously and whether the difference of variance average upon the realisation of the budget presents between 2009 and 2011. The type of research is descriptive-comparative by analysing quantitative data. The tools to analyse the data are analysis variance and hypothesa test of the difference between two averages. The research shows that the unfavourable budget was found on the material budget, direct payment to the workers, and project budget whitin 2009 and 2011. The test of hypothesa shows that the difference of variance average upon the realisation of the budget presents between  2009 and 2011 was not found.Kata kunci : : budgeting, realization, variance